2021
DOI: 10.3390/foods10071656
|View full text |Cite
|
Sign up to set email alerts
|

Ecklonia cava Extract Exerts Anti-Inflammatory Effect in Human Gingival Fibroblasts and Chronic Periodontitis Animal Model by Suppression of Pro-Inflammatory Cytokines and Chemokines

Abstract: Periodontitis is one of the most common chronic inflammatory diseases. The anti-inflammatory effect of the extract from brown algae Ecklonia cava was analyzed in lipopolysaccharide (LPS)-stimulated human gingival fibroblasts (HGF-1), the most abundant cells in gingival tissue. The gene expressions of cyclooxygenase-2 and interleukin-6 were decreased by 78 and 50%, respectively, at 100 μg/mL Ecklonia cava extract (ECE) treatment. The gene expressions of matrix metalloproteases (MMP-2 and MMP-8) and chemokines (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…of activated B cells (NF-κB) pathway. The other study confirmed that ECE inhibited the production of PGE 2 and reactive oxygen species (ROS) without cytotoxicity on human gingival fibroblast (HGF) (Jung et al, 2021). Another study investigated that Agarum clathratum, which has antioxidant and anti-microbial properties, exhibits potential for periodontitis treatment on Pg LPS-stimulated HGF (Han et al, 2021).…”
Section: Fisheries and Aquatic Sciencesmentioning
confidence: 83%
See 3 more Smart Citations
“…of activated B cells (NF-κB) pathway. The other study confirmed that ECE inhibited the production of PGE 2 and reactive oxygen species (ROS) without cytotoxicity on human gingival fibroblast (HGF) (Jung et al, 2021). Another study investigated that Agarum clathratum, which has antioxidant and anti-microbial properties, exhibits potential for periodontitis treatment on Pg LPS-stimulated HGF (Han et al, 2021).…”
Section: Fisheries and Aquatic Sciencesmentioning
confidence: 83%
“…Previous studies have confirmed that bioactive substances extracted from Phaeophyceae have therapeutic potential against periodontitis (Han et al, 2021;Jung et al, 2021;Kim et al, 2019b;Kim et al, 2021a;Magesh et al, 2020;Alden et al, 2022). Two of these studies investigated whether Ecklonia cava ethanol (EtOH) extract (ECE) has a therapeutic effect on periodontitis (Jung et al, 2021;Kim et al, 2019b).…”
Section: Trend Analysis Of Marine Bioactive Substances (Mbs) Against ...mentioning
confidence: 85%
See 2 more Smart Citations
“…The alga Ecklonia cava is an edible medicinal food that is widely consumed in Korea and Japan for its reported multiple health benefits that include anti-cancer [ 7 ], anti-diabetes [ 8 ], anti-inflammatory [ 9 ], and anti-obesity [ 10 ] properties. These studies from two publications suggest that the alga and isolated bioactive compounds might be safe for human consumption.…”
Section: Introductionmentioning
confidence: 99%